A style study of selected choral works of Ramon Pagayon Santos - Navarro, Joel Magus Pizana; Santos, Ramon Pagayon 1941-. ([S.l. s.n.], 2005)
This study involves the examination of the composer's training, exposure, major influences, compositional construct, and responses to interview questions prepared by this researcher. In so doing, Santos compositional style may be understood more contextually and defined more concretely. Thirteen of Santos choral works were pre-determined as representatives of the composer's most significant choral output. This collection dates from his early style as an emerging student composer to his most recent mature style. This study will uncover his use of traditional Philippine rituals and musical traditions, and innovative manipulation of text, rhythms, vocal technique, concepts of time and space, belief systems, and mythology.
A doctoral document submitted to Michigan State University in partial fulfillment of the requirements for the Degree of Doctor of Musical Arts.
Keywords: Music -- Analysis, appreciation; Style, Musical; Choral music; Composition (Music)